Arj nama-yi Malik al-Shuʿarāʾ Bahār - Bahār, "Malik al-shuʿarāʾ" Muḥammad Taqī, (Miras Maktoob, ISBN: 9789004365452., 2019)
Muḥammad Taqī "Malik al-shuʿarāʾ" Bahār (d. 1951) was a poet, a philologist and editor of ancient Persian texts, a publicist, and also a political activist. Born in Mashhad in 1856 and writing poetry since he was seven, he inherited the honorific title of poet laureate of Āstān-i Quds from his father, Malik al-shuʿarāʾ Ṣabūrī, in 1903. Malik al-shuʿarāʾ Bahār was active in the constitutional movement at the beginning of the twentieth century. He published activist poetry, was involved in various reformist newspapers and magazines, and saw the inside of a prison more than once, both in Qajar times and under Reza Shah. The present work is a collection of articles and documents in honour of Malik al-shuʿarāʾ Bahār with a focus on his significance as a philologist. Includes the first edition of his autobiography (in two versions), a bibliography, and a series of articles by various scholars in appreciation of his work as a philologist.